Impact of a multifaceted intervention to improve the clinical management of osteoporosis. The ESOSVAL-F study - Pascual de la Torre Manuel; Hurtado Isabel; Sanfélix-Gimeno Gabriel; Peiró Salvador; Sanfélix-Genovés José; Trillo-Mata José Luis; Giner-Ruiz Vicente (BMC, 2010)
Abstract Background A study to evaluate the impact of a combined intervention (in-class and on-line training courses, a practicum and economic incentives) to improve anti-osteoporosis treatment and to improve recordkeeping for specific information about osteoporosis. Methods/design A before/after study with a non-equivalent control group to evaluate the impact of the interventions associated with participation in the ESOSVAL-R cohort study (intervention group) compared to a group receiving no intervention (control group). The units of analysis are medical practices identified by a Healthcare Position Code (HPC) referring to a specific medical position in primary care general medicine in a Healthcare Department of the Region of Valencia, Spain. The subjects of the study are the 400 participating "practices" (population assigned to health care professionals, doctors and/or nurses) selected by the Healthcare Departments of the Valencia Healthcare Agency for participation as associate researchers in the ESOSVAL-R study (intervention group), compared to 400 participating "practices" assigned to primary care professionals NOT selected for participation as associate researchers in the ESOSVAL-R study, who are selected on the basis of their working in the same Healthcare Centers as the practices receiving the interventions (control group). The study's primary endpoint is the appropriateness of treatment according by the Spanish National Health System guide (2010) and the National Osteoporosis Foundation (NOF, 2008) and International Osteoporosis Foundation guidance (IOF, 2008). The study will also evaluate a series of secondary and tertiary endpoints. The former are the suitability of treatment and evaluation of the risk of fracture; and the latter are the volume of information registered in the electronic clinical records, and the evaluation of risks and the suitability of treatment.